Prevention of Oxaliplatin-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis - Peng, Siyu; Ying, Ariel Fangting; Chan, Nicholas Jian Hao; Sundar, Raghav; Soon, Yu Yang; Bandla, Aishwarya (Frontiers in Oncology, 2022)
Background: Oxaliplatin-induced peripheral neuropathy (OIPN) has significant clinical impact on the quality of life for cancer patients and is a dose limiting toxicity. Trials studying preventive measures have been inconclusive. A systematic review and meta-analysis were conducted to evaluate the existing pharmacological and non-pharmacological interventions to prevent chronic OIPN. Methods: Literature databases PubMed-MEDLINE, Embase and Scopus, were searched from 1 Jan 2005 to 08 Aug 2020 and major conferences’ abstracts were reviewed for randomized controlled trials that examined the efficacy of any preventive measure for OIPN. The primary outcome measure was the incidence of chronic OIPN with a preventive intervention as compared to placebo or no intervention. The pooled risk ratio and its 95% confidence interval were calculated using a random effects model. A network meta-analysis was conducted to derive indirect evidence of any preventive effect of an intervention against placebo when original trials compared one intervention against another. Results: Forty-four trials were analyzed describing 29 chemoprotective interventions, including combinations, and 1 non-pharmacological intervention. Ratings were assessed via a combination of outcomes with quality assessment using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) framework. Of the 30 interventions examined, there were six interventions supporting potential efficacy, 11 interventions with insufficient evidence and 13 interventions not recommended. Conclusion: Currently, there is insufficient certainty to support any intervention as effective in preventing OIPN. Of note is that most of these studies have focused on pharmacological interventions; non-pharmacological interventions are underexplored. Further research on ways to limit OIPN is needed.